Influence of Socio-Economic, Educational Status of School Children on their Information Seeking Behaviour and School Library Usage (A Study among G.C.E Advanced Level Students of the Jaffna Educational Zone) - Gobalasuthanthiran, K.; Sivarajasundaram, R.; Surenthirakumaran, R.; Chandrasekar, K. (Sri Lanka Library Review, 2016)
School libraries play a major role in seeking information for knowledge enhancement, by developing reading habits and information literacy skills among children, which are essential for life-long learning. This exploratory study intends to assess the influence of educational and socio-economic status of G.C.E (A/L) children on their information seeking behaviour, in addition to usage of school libraries. Randomly selected 442 students from G.C.E (A/L) classes of 20 schools in the Jaffna educational zone participated in the study. Multi-stage stratified random sampling method was adopted. Self-administered structured questionnaire was distributed to the sample population for data collection. In addition, data extraction form was used to evaluate the libraries in these selected schools. Collected data were analyzed using SPSS 17.0. Results revealed that school libraries are heavily used by the G.C.E (A/L) children for information seeking, irrespective of their educational and economic status of family. Descriptive analysis showed that reading textbooks is the prime purpose of visiting the school library, and majority visit the library 2-3 times in a week. Moreover, textbooks, newspapers and magazines were heavily used compared to other information resources available at school libraries. Evaluation of school libraries disclosed that most of the selected schools have adequate printed information resources and building facilities, whereas fund allocation, staff strength, electronic resource collection and infrastructure facilities are inadequate. Since this study revealed that school libraries are heavily used by the G.C.E (A/L) students, the respective authorities should take necessary action to enhance the library collection and accomplish the requirements mentioned above for the effective functioning of school libraries.
Keywords: Information seeking behaviour; School libraries